2012
DOI: 10.1158/0008-5472.can-12-0215
|View full text |Cite
|
Sign up to set email alerts
|

Alternate Splicing of the p53 Inhibitor HDMX Offers a Superior Prognostic Biomarker than p53 Mutation in Human Cancer

Abstract: Conventional high-grade osteosarcoma is the most common primary bone malignancy. Although altered expression of the p53 inhibitor HDMX (Mdmx/Mdm4) is associated with cancer risk, progression, and outcome in other tumor types, little is known about its role in osteosarcoma. High expression of the Hdmx splice variant HDMX-S relative to the full-length transcript (the HDMX-S/HDMX-FL ratio) correlates with reduced HDMX protein expression, faster progression, and poorer survival in several cancers. Here, we show th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 38 publications
2
61
1
Order By: Relevance
“…Notably, the frequency of p53-inactivating missense mutations (28) was lower in samples predicted to express MDM4 (4.6%) than in the nonexpresser samples (9.3%). This is consistent with previous observations that a low PSI index is associated with inactivating p53 mutations or MDM2 overexpression (29). However, this also indicates the presence in some cancers of p53-inactivating mutations in MDM4-expressing samples, an observation that is consistent with the p53-independent oncogenic functions of MDM4.…”
Section: Introductionsupporting
confidence: 92%
“…Notably, the frequency of p53-inactivating missense mutations (28) was lower in samples predicted to express MDM4 (4.6%) than in the nonexpresser samples (9.3%). This is consistent with previous observations that a low PSI index is associated with inactivating p53 mutations or MDM2 overexpression (29). However, this also indicates the presence in some cancers of p53-inactivating mutations in MDM4-expressing samples, an observation that is consistent with the p53-independent oncogenic functions of MDM4.…”
Section: Introductionsupporting
confidence: 92%
“…Although it has been suggested that mdmx-s RNA may act as a means of reducing full-length MDMX levels rather than being translated into protein, 20 we found that the mdmx-s transcript in our WD/DD LPS samples was translated into protein, albeit to varying extents.…”
Section: Mdmx Protein Expressioncontrasting
confidence: 84%
“…In this way, the ratio between the mdmx-s splice variant and the full-length mdmx becomes the means by which mdmx-s mRNA expression reduces that of the full-length MDMX protein, 19 and it has recently been reported that the reduced MDMX protein expression mediated by mdmx/mdmx-s is associated with a worse prognosis in patients with osteosarcoma. 20 The role of MDMX and MDMX-S in WD/DD LPS has not yet been defined. It has been reported that MDMX protein expression is very low in WD/DD LPS cell lines, 21 and MDMX gene amplification has been described in association with MDM2 co-amplification in one WD/DD LPS surgical specimen.…”
mentioning
confidence: 99%
“…Therefore, both studies reveal that MDMX predominantly adopts an inactive conformation for p53 binding. Our results also shed light on a puzzling observation that full-length MDMX is a poor inhibitor of p53 in reporter gene assays, whereas the MDMX-S alternative splice product without the central and C-terminal domains is a strong inhibitor of p53 and its expression in cancer correlates with poor prognosis (22).…”
Section: Discussionmentioning
confidence: 60%